Effects of storage temperature and duration on pollen grain viability and pollen-tube elongation in Chinese chinqapin (Castanea henryi Skan) - Xiong, Huan; Yuan, Deyi; Deng, Zhi-Yu; Niu, Genhua; Zou, Feng (Bangladesh Journal of Botany, 2020)
Chinese chinquapin [Castanea henryi (Skan) Rehder & E.H. Wilson] is used as a food and timber crop in southern China. Most chinquapin cultivars are self-incompatible and bloom at different times; consequently, artificial pollination is used to ensure fruit set and nut yield. Effective pollen storage that enables producers and breeders to use stored pollen for cross-pollination at a later date is important. In this study, the cultivar Changmangzi was used to estimate the viability and pollen tube length of pollen stored at room temperature, and at 4, −20, and −80°C using in vitro germination tests. It was observed that pollen grain germination significantly decreased at all four storage temperatures. Pollen viability was 14.4% after only 24 days of storage at room temperature. The germination rate was 13.3% after 90 days of storage at 4°C, and 14.5% after 180 days at −20°C. The initial germination rate of pollen stored at −80°C was 56.3% at the beginning of the test and decreased to 15.4% after 240 days. Pollen-tube length decreased with increased storage duration; mean pollen-tube lengths ranged from 109.44 to 257.51 μm. Based on these results, it is suggested that a storage temperature of −80°C for Changmangzi pollen is good.